PERAN FINTECH, INKLUSI KEUANGAN DAN LITERASI KEUANGAN TERHADAP KINERJA DALAM KESIAPAN DUKUNG CASHLESS SOCIETY SEKTOR USAHA MIKRO KECIL MENENGAH KABUPATEN BEKASI - Zaenudin, Ahmad; Fahamsyah, Mohammad Hatta (Jurnal Investasi, 2023)
ABSTRACT - Less cash society is a term used by Bank Indonesia in relation to a non-cash society, where groups of people are used to using non-cash payment instruments, especially in economic activities. Cash payments which were the main means of transaction have now been shifted to non-cash payments based on cards, electronic and paper. With the change in the non-cash payment system, it brought several conveniences to the community and this was able to encourage Bank Indonesia to create a less cash society. This research aims to analyze the role of fintech on MSMEs in Bekasi Regency, analyze the impact of financial inclusion on MSMEs in Bekasi Regency and analyze the effect of financial literacy on MSMEs in Bekasi Regency. The research method in this study uses a quantitative approach. With the sampling technique using dsample used using non-probability sampling techniques. The population in this research were SMEs in Bekasi Regency, with a total sample of 100 SMEs in Bekasi Regency. Analysis using SPSS version 23.0. With the results of the study, namely that there is no impact of fintech on MSME performance, there is a significant influence between financial inclusion on financial performance and there is an impact of financial literacy on MSME performance.